Are Global Imbalances Sustainable? Post-Crisis Scenarios - de Mello, Luiz (OECD Economics Department Working Papers, 2010)
This paper assesses the sustainability of global imbalances by testing for the presence of unit roots in the current account positions (measured in relation to GDP) of the United States, China, Japan, Germany and the oil-exporting countries using a methodology that allows for structural breaks in levels and trends. We find that the external positions of these major countries/regions are stationary around structural breaks, which define episodes of current account reversals. On the basis of an event analysis of past reversals, it appears that structural breaks are associated with shifts in the fiscal stance, exchange rate parities and potential output growth, a finding that underscores the scope for macroeconomic and structural policies to ensure the sustainability of external positions while avoiding potentially disruptive reversals. These findings have implications for long-term capital flows after the crisis